Novel Protocol for the Chemical Synthesis of Crustacean Hyperglycemic Hormone Analogues — An Efficient Experimental Tool for Studying Their Functions - Mosco, Alessandro; Zlatev, Vientsislav; Guarnaccia, Corrado; Pongor, Sándor; Campanella, Antonella; Zahariev, Sotir; Giulianini, Piero G. (PLOS ONE, 2012)
The crustacean Hyperglycemic Hormone (cHH) is present in many decapods in different isoforms, whose specific biological functions are still poorly understood. Here we report on the first chemical synthesis of three distinct isoforms of the cHH of Astacus leptodactylus carried out by solid phase peptide synthesis coupled to native chemical ligation. The synthetic 72 amino acid long peptide amides, containing L- or D-Phe3 and (Glp1, D-Phe3) were tested for their biological activity by means of homologous in vivo bioassays. The hyperglycemic activity of the D-isoforms was significantly higher than that of the L-isoform, while the presence of the N-terminal Glp residue had no influence on the peptide activity. The results show that the presence of D-Phe3 modifies the cHH functionality, contributing to the diversification of the hormone pool.